Data story : explain data and inspire action through story - Duarte, Nancy (Ideapress Publishing, 2019)
What if you sliced data and found a huge problem or opportunity? Data did its job, but now it needs a storyteller. The way insights are communicated could reverse or increase the trajectory of data. The actions you ask others to take today can change your future data. But getting others to move forward with those actions only happens when someone communicates well. Learn effective ways to turn your data into narratives that blend the power of language, numbers, and graphics. This book is not about visualizing data, there are plenty of books covering that. Instead, you'll learn how to transform numbers into narratives to drive action, and help communicate data in a way that creates outcomes both inside and outside your own organization
Keywords: společenské vědy; prezentace informací; data; social sciences; presentation of information; monografie; monographs